Renal Dysfunction as a Predictor of Slow-Flow/No-Reflow Phenomenon and Impaired ST-Segment Resolution after Percutaneous Coronary Intervention in ST- Elevation Myocardial Infarction. A Retrospective Analysis - Muhammad Abbas Khan, Samiullah, Jaghat Ram, Javed Khurshed Shaikh, Muhammad Hasan Butt, Mahmood Ul Hassan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The research aimed to examine the relationship between kidney dysfunction and the occurrence of slow blood flow or no-reflow phenomenon and insufficient ST-segment resolution after the percutaneous coronary intervention procedure in individuals suffering from ST-elevation myocardial infarction. Methods: In a retrospective analysis conducted at Hayatabad Medical Complex Peshawar, for six months, 210 consecutive patients have undergone percutaneous coronary intervention (PCI) for ST-elevation myocardial infarction (STEMI). The term slow-flow/no-reflow referred to an angiogram result of TIMI Grade <3 after the implantation of a stent, despite a residual stenosis of less than 50%, and with no major damage or visible blood clots. Results: The study included 210 patients, with 185 (88.0%) having normal flow and 25 (11.9%) having slow flow/no-reflow after PCI. Comparison between patients with normal flow and those with slow flow or no-reflow. Male sex was more common in the LVEF ≥50% group compared to the LVEF <50% group (84.2% vs. 74.0%, p=0.043). Practical Implication: Overall, the practical implications of this study can positively impact the community by enhancing risk assessment, patient management, treatment approaches, communication, and future research in the context of renal dysfunction and PCI outcomes in STEMI patients. Conclusion: The study found that patients with STEMI who have renal dysfunction are more likely to experience SFR and ISR after undergoing PCI. We should regard renal dysfunction as a significant factor that increases the risk of these complications. Treatment may need to be more intensive to achieve better results in these patients. Keywords: Renal dysfunction, slow-flow/no-reflow phenomenon, inadequate ST-segment resolution,